Institutional delivery rate and associated factors among women in rural communities: analysis of the 2017–2018 Bangladesh Demographic and Health Survey - Agani Afaya; Meherun Nesa; Jotsna Akter; Taewha Lee (BMJ Open)
Background Institutional delivery rate among women in rural communities in Bangladesh remains low after several governmental interventions. A recent analysis of maternal mortality in Bangladesh revealed that women in rural communities were more likely to die from maternal complications than those in urban areas.Objective This study assessed the institutional delivery rate and associated factors among women in rural communities in Bangladesh.Design This was a cross-sectional study that used the 2017–2018 Bangladesh Demographic and Health Survey for analysis. To determine the factors associated with institutional delivery, multivariate logistic regression analysis was performed.Setting and participants The study was conducted in Bangladesh and among 3245 women who delivered live births 3 years before the survey.Main outcome measure The outcome variable was the place of delivery which was dichotomised into institutional and home delivery/other non-professional places.Results The institutional delivery rate was 44.82% (95% CI 42.02% to 47.65%). We found that women between the ages of 30 and 49 years (aOR=1.51, 95% CI 1.05 to 2.18), women whose partners attained higher education (aOR=2.02, 95% CI 1.39 to 2.94), women who had antenatal visits of 1–3 (aOR=2.54, 95% CI 1.65 to 3.90), 4–7 (aOR=4.79, 95% CI 3.04 to 7.53), and ≥8 (aOR=6.13, 95% CI 3.71 to 10.42), women who watched television (aOR=1.35, 95% CI 1.09 to 1.67) and women in the middle (aOR=1.38, 95% CI 1.05 to 1.82), rich (aOR=1.84, 95% CI 1.34 to 2.54) and richest (aOR=2.67, 95% CI 1.82 to 3.91) households were more likely to use institutional delivery. On the other hand, women who were working (aOR=0.73, 95% CI 0.60 to 0.89), women who were Muslims (aOR=0.62, 95% CI 0.44 to 0.89) and women who gave birth to two (aOR=0.61, 95% CI 0.48 to 0.77) or ≥3 children (aOR=0.46, 95% CI 0.35 to 0.60) were less likely to use institutional delivery.Conclusion The study revealed that a low proportion of women in rural communities in Bangladesh used institutional delivery. The results of this study should be taken into account by policy-makers and governmental efforts when creating interventions or programmes aimed at increasing institutional delivery in Bangladesh.